PELAYANAN MEDIS PASIEN RAWAT INAP PADA RUMAH SAKIT UMUM DAERAH ARIFIN AHMAD PEKANBARU - RESSA APRIANA; ZAILI RUSLI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study intends to find out how the medical services provided in the inpatient General Hospital Arifin Ahmad Pekanbaru. The research is motivated by the availability of human resources and medical facilities that have not been able to provide health services to the user with the maximum health of the public service and there are still complaints from the public. It can be see from some other indication of the presence unfair officers in providing services and still no service ethic is not polite and friendly .The method used in this research is descriptive qualitative . Researchers are trying to reveal the facts in accordance with the fact that there is no intervention for the condition occurs . The theory used in this study is that Supranto theory regarding the quality of service that is characteristic of Reliability ( reliability), responsiveness (responsiveness), Assurance (collateral), Empathy (attention), Tangibles (real evidence) .The conclusion of this study is good enough This suggests that the implementation of medical services in inpatient General Hospital Arifin Ahmad Pekanbaru has various drawbacks .Key Words : Inpatient Medical Services, General Hospital Arifin Ahmad,Pekanbaru